Evaluasi Luaran Klinis Pasien dan Karakteristik Pasien Frozen Shoulder yang Menjalani Prosedur Shoulder Arthroscopy - Rawung, Rangga B. V.; Lampus, Harsali; Kambey, Stefan; Bagy, Raynald; Sundah, Antony; Tooy, Christorei D. (Universitas Sam Ratulangi, 2026)
Abstract: Frozen shoulder is characterized by a gradual increase in pain with spontaneous onset and limited range of motion in the glenohumeral joint. Arthroscopic capsular release is a most well-known technique with favorable outcomes for frozen shoulder. This was a single-center retrospective study examining the clinical outcomes of frozen shoulder cases undergoing arthroscopy at Prof. Dr. R. D. Kandou General Hospital in Manado from February 2025 to October 2025. The results showed that a total of 26 patients were included in this study. At preoperative assessment, pain levels averaged 4.96 ± 0.96 (median 5.00 [5.00–5.75]; range 3–6). Initial range of motion (ROM) showed significant limitations. At follow-up, an improvement in ROM was clearly observed. In conclusion, shoulder arthroscopy in patients with frozen shoulder results in a significant improvement in ROM from the first month and persisted until the third month after surgery indicating that arthroscopic capsular release is an effective surgical treatment option. Keywords: frozen shoulder; shoulder arthroscopy; range of motion Abstrak: Frozen shoulder ditandai dengan peningkatan nyeri secara bertahap dengan onset spontan dan keterbatasan dalam range of motion (ROM) sendi glenohumeral. Pelepasan kapsul artroskopi merupakan teknik yang paling terkenal dengan hasil yang baik untuk frozen shoulder. Penelitian ini bertujuan untuk melihat luaran klinis dari kasus frozen shoulder yang menjalani prosedur shoulder arthroscopy di RSUP Prof Dr. R. D. Kandou Manado pada periode Februari 2025 – Oktober 2025. Jenis penelitian ialah retrospektif single center studi. Hasil penelitian mendapatkan sebanyak 26 pasien dilibatkan dalam penelitian ini. Pada penilaian pra operasi, kadar nyeri berada pada rerata 4,96±0,96 (median 5,00 [5,00–5,75]; rentang 3–6). Nilai ROM awal menunjukkan keterbatasan bermakna. Pada tindak lanjut, peningkatan nilai ROM terlihat jelas. Simpulan penelitian ini ialah prosedur shoulder arthroscopy pada pasien frozen shoulder memberikan peningkatan bermakna pada ROM yang sudah tampak sejak bulan pertama dan bertahan hingga bulan ketiga pascaoperasi yang menunjukkan bahwa arthroscopic capsular release merupakan pilihan tatalaksana operatif yang efektif. Kata kunci: frozen shoulder; shoulder arthroscopy; range of motion